Micro-abrasive wear behavior by ball cratering on MAO coating of Ti–25Ta alloy - Kuroda, Pedro Akira Bazaglia; de Mattos, Felype Narciso; Grandini, Carlos Roberto [UNESP]; Afonso, Conrado Ramos Moreira (Elsevier, 2023)
Surface treatments are widely used techniques to improve the wear resistance of titanium alloys for biomedical applications. Modification by micro-arc oxidation (MAO) creates an oxide ceramic coating of alloy substrate to improve wear resistance. This work investigated the micro-abrasive wear by ball cratering of MAO coatings over Ti–25Ta alloy. For this purpose, the surfaces were worn by steel balls at a load of 2 N and a rotation speed of 200 rpm. After 50 min of testing, the depth of the wear reaches the substrate, confirming that the MAO coating has a much lower wear rate. Guided by Archard's law, the wear volume, wear rate, and MAO coating thickness were calculated through wear test.
Keywords: Ball cratering; Micro-arc oxidation; Ti–25Ta alloy